2010
DOI: 10.1007/s00044-010-9340-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic activity of novel benzopyrano[3,2-c]chromene-6,8-dione derivatives

Abstract: 4-Hydroxycoumarins constitute the structural nucleus of many natural products, drugs, and pesticides. Promising biological properties in new families of synthetic coumarins were recently reported. Therefore, efficient synthesis of new benzopyrano[3,2-c]chromene-6,8-dione was undertaken and the structures of 15 compounds were confirmed by their IR, Mass, 1 H-NMR, and C, H, N analysis. Then, the cytotoxic activities of these compounds were assessed on four different human cancer cell lines (Raji, HeLa, LS180, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…All products were identified by comparison with authentic samples. [16] These results demonstrate that both the yields and the reaction time are relatively independent of the position of the substituent in aryl aldehyde. However, nitrobenzaldehyde had relatively better yields.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…All products were identified by comparison with authentic samples. [16] These results demonstrate that both the yields and the reaction time are relatively independent of the position of the substituent in aryl aldehyde. However, nitrobenzaldehyde had relatively better yields.…”
Section: Introductionmentioning
confidence: 90%
“…[15] We have recently reported design, synthesis and toxicity effect of novel benzopyrano [3,2-c]chromene-6,8-diones 4 derivatives (Scheme 1). [16] In continuation of our attempts to develop selective and preoperatively useful methodology, using heteropolyacids as green catalysts in various organic reactions, [17] we report a rapid and convenient method for synthesis of these compounds, catalyzed by heteropolyacids (HPAs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the pyrimidines and coumarins exhibit diverse biological properties (Kulkarni et al, 2006;Shafiee et al, 2010). It was observed that linking of these two active pharmacophores would generate novel molecular templates which are likely to exhibit interesting biological properties in animal models (Keri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported the synthesis and cytotoxic activity of novel coumarin derivatives, chromeno [4,3-b]-quinolines, benzopyrano [3,2-c]chromene-6,8-diones and chromeno [3',4']pyrano [2,3-b]quinoline-6,9-diones [8][9][10]. In continuation of our studies, and owing to the importance of chromenopyridines, we decided to investigate the synthesis of new 5-oxo-5H-chromeno [4,3-b]pyridine derivatives by a simple method.…”
mentioning
confidence: 99%